Some features of alt texts associated with images in Web pages - Timothy C. Craven (Information Research: An International Electronic Journal, 2006)
Introduction. This paper extends a series on summaries of Web objects, in this case, the alt attribute of image files. Method. Data were logged from 1894 pages from Yahoo!'s random page service and 4703 pages from the Google directory; an img tag was extracted randomly from each where present; its alt attribute, if any, was recorded; and the header for the corresponding image file was retrieved if possible. Analysis. Associations were measured between image type and use of null alt values, image type and image file size, image file size and alt text length, and alt text length and number of images on the page. Results. 16.6% and 17.3% of pages respectively showed no img elements. Of 1579 and 3888 img tags randomly selected from the remainder, 47.7% and 49.4% had alt texts, of which 26.3% and 27.5% were null. Of the 1316 and 3384 images for which headers could be retrieved, 71.2% and 74.2% were GIF, 28.1% and 20.5%, JPEG; and 0.8% and 0.8% PNG. GIF images were more commonly assigned null alt texts than JPEG images, and GIF files tended to be shorter than JPEG files. Weak positive correlations were observed between image file size and alt text length, except for JPEG files in the Yahoo! set. Alt texts for images from pages containing more images tended to be slightly shorter. Conclusion. Possible explanations for the results include GIF files' being more suited to decorative images and the likelihood that many images on image-rich pages are content-poor.